Forecast uncertainty and ensemble spread in surface currents from a regional ocean model - Idžanović, Martina; Rikardsen, Edel S. U.; Röhrs, Johannes (Frontiers in Marine Science, 2023)
An operational ocean ensemble prediction system (EPS) for the coastal seas off Northern Norway is evaluated by comparing with high-frequency-radar current speed estimates. The EPS is composed of 24 members for which the ocean current is not perturbed nor constrained but forced with an atmosphere ensemble. The ocean ensemble spread stems from (i) accumulated differences in wind-forcing history and (ii) constraints of sea surface temperature by data assimilation. The intention of the ensemble is to reflect the actual uncertainty in initial conditions, which are largely unknown in terms of mesoscale circulation. We find a low but pronounced predictive skill in surface currents along with a good statistic skill. Additionally, current speeds show deterioration of the validation metrics over the forecast range. Further, high-resolution wind forcing seems to provide better forecast skill in currents compared to lower resolution forcing. In general, the ensemble exhibits the ability to predict forecast uncertainty.